Implementasi Program Asrama dalam Mewujudkan Karakter Peserta Didik - Choirotun Ni'mah, Siti (PT Faliha Cendekia Nusantara, 2024)
Character coaching and character development can motivate learners to do positive things. The implanting of character is not only cultivated through knowledge and practice, but must be habit. One of the efforts to form a character through the dorm program. From the applied dormitory program may help in developing learners' characters because they are unconsciously used to a continuous program of dorms. Through breeding, it is expected that learners habitually approach everything by reflecting known character values. The purpose of the study to find out is the dorm program, the character of the student and the retard factors and the implementation factors of the dorm program in emulation of the student character. The study employs qualitative methods, using field reseacrh. And data is obtained through documentation, observation, and interviews. Then the data is analyzed with data reduction, data presentation, and conclusions or verification. Results from the study indicate that the implementation of the dormitory program in ma of the skills as-sa 'adah pamotan program greatly affected developing the character of learners. With the environment, adequate facilities and infrastructure provide support for the run of the dorms program to create a character for religious learners, discipline, tolerance, compassion.